Geometric Registration of High Spatial Resolution Images Based on Google Earth Image and Global DEM Data - J T Zang (Lowland Technology International, 2020)
With the development of remote sensing technology, theapplication of remote sensing technology is expanding. Beforethe application of remote sensing images, geometric registrationand other preprocessing are often required for tilt correction andprojection error correction, which often requires the selection ofground control points. Given the lack of measured groundcontrol points, the correction accuracy will be greatly limited. Inthis paper, a remote sensing image orthographic correctionprocess based on Google earth and Global DEM is proposed.First, in ENVI5.3, the image to be corrected and the referenceimage (Google Earth image) were automatically matched withthe corresponding ground object points to obtain the coordinatefile of the correction control point (.pts), and the coordinateswere converted to plane coordinates. Under the ArcGIS10.2platform, the data of the coordinate table of the correctioncontrol points were converted into the ArcGIS point file (SHP).Finally, the point file was spatially superimposed with theelevation data of Global DEM to obtain the elevation value, andthen the ground control point file with elevation value wasobtained, and then the orthographic correction with controlpoints was carried out. The result showed that compared withthe orthophoto correction without control points, the processingprocess adopted in this paper can improve the accuracy ofcorrection, and the accuracy can meet the requirements of the1:10000 land survey in the working base map. This research isexpected to provide a new method for obtaining high-qualitydigital orthophoto images needed for land surveys.